Adverse Rohingya Impacts on Bangladeshi Economy and its Solutions - Dey, Sudip (American Journal of Trade and Policy, 2018)
Rohingya crisis is a crucial topic for recent time in world media. Due to injustice massacre on Rohingya, they took place in our country. This massacre was illegal and breaks the law of human rights. After arriving the Rohingya in Bangladesh, I have seen it had some adverse economic impacts on our Bangladeshi economy. From my study, I have seen it has effects on our tourism industry, unemployment, price hiking, banking sector, food security, and environment and so on. But the impact of Rohingya crisis on tourism industry was intolerable. At the end of my study, I have suggested some polices to solve the Rohingya crisis.
Keywords: Rohingya; Myanmar; persecution; economic impacts; solution; international organizations